Modification of Lhx2 activity for ex vivo amplification of human iPSC-derived hematopoietic stem/progenitor cells - Kitajima, Kenji; Takahashi, Yuna; Ando, Hikaru; Shingai, Minako; Hamasaki, Mako; Tanikawa, Miyu; Kanokoda, Mai; Nakajima, Marino; Nishito, Yasumasa; Hara, Takahiko (Frontiers in Cell and Developmental Biology, 2024)
Hematopoietic stem cells (HSCs) obtained from patient-derived human induced pluripotent stem cells (iPSCs) are a promising tool for curing various hematological disorders. We previously demonstrated that enforced expression of the LIM-homeobox transcription factor Lhx2, which is essential for mouse embryonic hematopoiesis, leads to generation of engraftable and expandable hematopoietic stem cells (HSCs) from mouse iPSCs. However, it remained unknown whether Lhx2 can induce HSCs from human iPSCs. Here, we investigated the effect of Lhx2 overexpression on hematopoietic differentiation of human iPSCs. Unexpectedly, Lhx2 severely inhibited proliferation of human iPSC-derived hematopoietic cells. Thus, Lhx2 exhibited differential effects on mouse and human hematopoietic cells. Further studies implied that the inhibitory effect of Lhx2 on human iPSC-derived hematopoietic cells was due to insufficient transcriptional activation ability. Therefore, we modified Lhx2 to strengthen its activity as a transcriptional activator. This modified Lhx2 could induce ex vivo amplification of human iPSC-derived hematopoietic stem/progenitor cells (HSPCs). We believe that these findings will facilitate the development of a method to efficiently produce HSCs from human iPSCs.